The types of grafts used in surgical treatment and effects of physical therapy treatment in athletes with ACL rupture (Research, Society and Development, 2023)
The anterior cruciate ligament (ACL) injuries and their treatments have been much discussed, considering that it is one of the most frequent injuries in the knee. This fact occurs due to its biomechanical importance in this joint. Therefore, this study aimed to analyze the effects of pre- and postoperative treatments and their influence on the ACL recovery process. This was an integrative literature review. The search was conducted by online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services databases, from September to December 2022. Regarding the process of ACL recovery, it is important to emphasize the pre-surgical rehabilitation, seeking to restore neuromuscular function and proprioception of the knee, in addition to strengthening thigh muscles, such as the quadriceps, which will be important for the follow-up of the post-surgical rehabilitation process until the return to sports. During surgery, two main techniques are used as grafting, the patellar-tendon-bone (PTO) technique and the semitendinosus and gracilis quadruple graft (EQSG). Finally, a post-surgical rehabilitation with a period of at least 8 months without returning to sports. We conclude that the main types of grafts used are the OTO and EQSG. The quadriceps tendon (TO) was shown to be a viable option for treatment, however, the OTO autograft is currently the most indicated for the surgical process of ACL rupture.